2017
DOI: 10.1108/ejim-06-2017-0077
|View full text |Cite
|
Sign up to set email alerts
|

The roles of CEO transformational leadership and organizational factors on product innovation performance

Abstract: Purpose The purpose of this paper is to examine the direct and indirect effects of CEO transformational leadership on product innovation performance. This research investigates the mechanism between CEO transformational leadership and product innovation performance, to understand the process through which transformational CEOs exert their influence. Design/methodology/approach This study is a quantitative research. Data were collected from 269 manufacturing firms in Thailand through a mail survey. This resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(54 citation statements)
references
References 108 publications
(125 reference statements)
3
45
0
4
Order By: Relevance
“…It could thus be argued that transformational leadership has an impact on the foundations of innovation as the transformational leadership impacts the culture in organisation. In defining a clear vision for the organisation, transformational leadership including the CEO direction and vision for the organisation sets up the culture that eventually influences organisational direction including the culture and behaviour of the employees (Sattayaraksa & Boon-itt, 2017). This is an important factor as the culture in the organisation potentially leads employees to always think of innovation in their processes and activities thereby leading to increased innovation in the organisation (Sattayaraksa & Boon-itt, 2017).…”
Section: Vision and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…It could thus be argued that transformational leadership has an impact on the foundations of innovation as the transformational leadership impacts the culture in organisation. In defining a clear vision for the organisation, transformational leadership including the CEO direction and vision for the organisation sets up the culture that eventually influences organisational direction including the culture and behaviour of the employees (Sattayaraksa & Boon-itt, 2017). This is an important factor as the culture in the organisation potentially leads employees to always think of innovation in their processes and activities thereby leading to increased innovation in the organisation (Sattayaraksa & Boon-itt, 2017).…”
Section: Vision and Culturementioning
confidence: 99%
“…In defining a clear vision for the organisation, transformational leadership including the CEO direction and vision for the organisation sets up the culture that eventually influences organisational direction including the culture and behaviour of the employees (Sattayaraksa & Boon-itt, 2017). This is an important factor as the culture in the organisation potentially leads employees to always think of innovation in their processes and activities thereby leading to increased innovation in the organisation (Sattayaraksa & Boon-itt, 2017). In addition, the culture of innovation has an impact on the approach of employees with an innovative thinking culture being a driver of the resulting innovation of the organisation (Sattayaraksa & Boon-itt, 2017).…”
Section: Vision and Culturementioning
confidence: 99%
See 1 more Smart Citation
“…In this context, Lentz (1981) looked at a more comprehensive notion of organizational performance from multidisciplinary perspective notably (i)environment-performance linkage, (ii) environment and organization structure, (iii) structure of an organization as principal determinant of performance, (iv) strategy, organization structure and performance, (v) environment, strategy and performance (vi) administration and performance. Besides that, other dimension such as transformational leadership and product innovation performance (19) and intellectual capital-knowledge management (20) also had been discussed with regard to organizational performance. Nevertheless, effectiveness and efficiency remain as the focal point of all organizational theories (21).…”
Section: Organizational Performance In the Public Sectormentioning
confidence: 99%
“…This calls for a research into this; but more importantly, the study is premised on the fact that, investigations into the factors affecting innovation have been the concern of numerous empirical studies (e.g. Anderson, Potočnik & Zhou, 2014;Molina-Castillo& Manuera-Aleman, 2009) and there has been some researches which have established relationships between transformational leadership and innovation culture (Sattayaraksa & Boon-itt, 2018;Xeniko, 2017). Research has shown that under certain market conditions, firms are able to innovate and also learn new ways of doing things.…”
Section: Introductionmentioning
confidence: 99%